2020
DOI: 10.18632/aging.103146
|View full text |Cite
|
Sign up to set email alerts
|

KIF23 activated Wnt/β-catenin signaling pathway through direct interaction with Amer1 in gastric cancer

Abstract: Increased expression of the kinesin family member 23 (KIF23) has been verified in gastric cancer (GC) and its upregulation contributes to cell proliferation. Even though, the role of KIF23 has not been fully elucidated in GC, and the mechanisms of KIF23 as an oncogene remain unknown. To further identify its potential role in GC, we analyzed gene expression data from GC patients in GEO and TCGA datasets. KIF23 was upregulated in GC, and increased expression of KIF23 correlated with poor prognosis. Importantly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 33 publications
(37 reference statements)
3
44
0
Order By: Relevance
“…In the nucleus, β-catenin interacts with TCF/LEF family proteins to form the β-catenin-TCF4 complex, which eventually activates a series of downstream genes related to cell proliferation and metastasis, such as c-Myc and cyclin D1 41 , 42 . Moreover, some studies have found that KIF23 promotes the proliferation of gastric cancer cells through the Wnt/β-catenin signaling pathway 43 . We observed the same phenomenon in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the nucleus, β-catenin interacts with TCF/LEF family proteins to form the β-catenin-TCF4 complex, which eventually activates a series of downstream genes related to cell proliferation and metastasis, such as c-Myc and cyclin D1 41 , 42 . Moreover, some studies have found that KIF23 promotes the proliferation of gastric cancer cells through the Wnt/β-catenin signaling pathway 43 . We observed the same phenomenon in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Among the included lncRNAs, LINC00501 and LINC00365 were associated with the most miRNAs, suggesting that they may be key regulators of GC due to their ceRNA functionality. Previous studies have demonstrated that a number of the selected mRNAs and predicted miRNAs, including miR-301b-3p ( 31 ), miR-4295 ( 32 ), miR-206 ( 33 ), miR-613 ( 34 ), miR-429 ( 35 ), forkhead box C1 ( 36 ), G protein-coupled receptor class C group 5 member A ( 37 ) and kinesin family member 23 ( 38 ), are associated with GC. GO analysis revealed that the 114 mRNAs within this network may be involved in biological processes, including ‘biological regulation’, ‘metabolic process’, ‘response to stimulus’, ‘multicellular organismal process’, ‘cell communication’, ‘developmental process’, ‘localization’, ‘cellular component organization’, ‘cell proliferation’, ‘reproduction’ and ‘multi-organism process growth’.…”
Section: Discussionmentioning
confidence: 99%
“…KIF11 knockdown inhibits the migration and invasion of BC cells via decreasing the phosphorylation of ERK, AMPK, AKT, and CREB ( 47 ). KIF23 promotes gastric cancer cell proliferation, migration, and invasion by activating Wnt/β-catenin signaling pathway through direct interaction with Amer1 ( 48 ). The expression levels of CCNA2, CDK2, and PCNA were reduced in cells with knockdown of EZH2 or NSD2, while the expression levels of KIF11and KIF23 were only reduced in cells with knockdown of EZH2, suggesting that CCNA2, CDK2, and PCNA may be regulated by both EZH2 and NSD2.…”
Section: Discussionmentioning
confidence: 99%